Downward Nominal Wage Rigidity in Europe : An Analysis of European Micro Data from the ECHP 1994-2001 - Christoph Knoppik; Thomas Beissinger (Institute for the Study of Labor (IZA), 2005)
This paper substantially extends the limited available evidence on existence and extent of downward nominal wage rigidity in the European Union and the Euro Area. For this purpose we develop an econometric multi-country model based on Kahn?s (1997) histogram-location approach and apply it to employee micro data from the European Community Household Panel (ECHP) for twelve of the EU?s current member states. Our estimates for the degree of downward nominal wage rigidity on the national as well as the EU-wide level point to marked downward nominal wage rigidity within the European Union.
Keywords: E24; J30; 330; downward nominal wage rigidity; wage stickiness; European Community Household Panel; ECHP; histogram-location approach; European Union; Lohnrigidität; Nichtparametrisches Verfahren; Schätzung; EU-Staaten; histogramm-location approach